Effect of operating conditions on the bursting performances of cross-grooved domed rupture disc - Shuying Feng; Zhaijun Lu; Shuang Wu; Jiefu Liu (Scientific Reports)
Abstract The cross-grooved domed rupture disc (CDR) is widely used due to its rapid response and the absence of fragment spattering. The bursting performance of the CDR is primarily affected by the operating conditions including the applied pressure, clamp fillet radius, and pressure rise rate. In this study, a systematic investigation was conducted to examine the dynamic bursting pressure (DBP) of the CDR under varying operating conditions. A numerical model of the CDR was developed and validated against the dynamic bursting test results. The applied pressure conditions, including the operating pressure and back pressure, were thoroughly analyzed. The results indicate that an increase in applied pressure leads to a decrease in DBP. In certain cases, the presence of back pressure can cause premature failure. This behavior is attributed to the combined effects of residual stress and plastic deformation. Furthermore, due to shear stress at the boundary, the DBP of the CDR decreases as the clamp fillet radius increases. Finally, as the pressure rise rate increases, the DBP initially rises and then declines, which can be attributed to the strain rate effect of the material.